A MODEL PEMBELAJARAN ACTIVE LEARNING TIPE SNOWBALL THROWING DAN TIPE INDEX CARD MATCH (ICM) TERHADAP PEMAHAMAN KONSEP SISWA PADA PEMBELAJARAN IPS DI SEKOLAH DASAR - Rifqi Abdul Basit; Enok Maryani (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2020)
Mastery of learning materials is one of the main goals in education. The purpose of this study was to determine the effectiveness of the active learning model snowball throwing type with the index card match type in the ability to understand the concept of learners in elementary school. This research was conducted on students in grade IV SDN Cikampek Barat II, Cikampek District, Karawang City. The number of participants in this study were 26 students in the experimental class 1 who applied the snowball throwing learning model and as many as 26 students in the experimental class 2 who used the index card match learning model. The research method used in this study is a quasi-experimental method with the matching pretest posttest control group design. The data of this study were collected using test instruments and assessment rubrics. Based on the results of the study, it can be concluded that the index card match learning model is more effective in increasing students' understanding of the concept of existing home material and traditional Indonesian clothing compared to the snowball throwing learning model.